Draft Sixth Five Year Plan 1980-85 and Annual Plan 1981-82 Volume-I, Government of West Bengal - Planning Commission (Planning Commission, 1980)
The Government of West Bengal had formulated in December 1978 the draft of a Five-Year Plan, covering the period 1978-83 for the State in terms of a request from the then Planning Commission. The problems confronting the economy of the State were analysed in detail in that draft- As a consequence of the change of regime at the Centre, the Planning Commission too-has been reconstituted, and the draft of the national Five-Year Plan for 1978-83 has been abandoned. It is now proposed to formulate a new Plan covering the period 1980-85. The State Government has been asked by the Planning Commission to forward its Plan proposals with respect to this new period. The present document has been prepared pursuant to this request. Since the genre of the problems has not altered in the past two years, it is suggested that this document should be considered along with the document Five-Year Plan 1978-83 : West Bengal presented in December 1978.
Draft Sixth Five Year Plan 1980-85 and Annual Plan 1981-82 Volume-I
Government of West Bengal